BETA-DIVERSITY ANALYSIS OF A BIRD ASSEMBLAGE OF A BIODIVERSITY HOT-SPOT WITHIN THE ATLANTIC FOREST - Tonetti, Vinicius Rodrigues [UNESP]; Cavarzere, Vagner (Neotropical Ornithological Soc, Usgs Patuxent Wildlife Research Ctr, 2017)
The Atlantic Forest, a biodiversity hotspot, is the second largest tropical rainforest in South America. It harbors the greatest number of threatened and endemic bird species in Brazil. Serra de Paranapiacaba is one of the best-preserved and largest forest remnants, inserted within the Serra do Mar massif. Despite its undoubted importance for bird conservation, ornithological knowledge in the region is still scattered across different studies. The aim of this article is to report bird species richness in the Serra de Paranapiacaba and to compare it with 19 other well- preserved and well- sampled Atlantic Forest localities via multivariate analysis to synthesize ornithological knowledge in the region. We compiled bird records from the literature and provide our own records based on surveys and non-systematic observations at three localities between 2010 and 2017. We performed a Hierarchical Cluster and a Principal Coordinate analysis with bird communities to infer avifauna affnities of Serra de Paranapiacaba and other Atlantic Forest regions with different vegetation types. Overall, we compiled records for 479 species, 144 of which are endemic to Atlantic Forest and 15 which are threatened at global level. The Serra de Paranapiacaba bird community is more similar to that of localities where vegetation is montane ombrophilous dense forest and mixed ombrophilous forest and, to a lesser extent, to semi-deciduous and restinga forest. Our study corroborates a division of southern and northern counterparts of some bird species along Serra do Mar as proposed by other authors. We suggest the Guapiara Plateau and Paranapiacaba Ridge, in Sao Paulo state, as barriers of these assemblages. Finally, we confirm the importance of the region for the conservation of Atlantic Forest birds and updated the data used to classify it as an Important Bird Area (IBA).
Keywords: Aves; Brazil; Conservation; Habitat fragmentation; Hierarchical Cluster Analysis; Multivariate Analysis; Principal Coordinate Analysis; Serra de Paranapiacaba